Beyond metropolises: artificial intelligence awareness and educational needs among medical students in a developing country - Sanri, Emre (Frontiers in Medicine, 2025)
BackgroundWhile artificial intelligence (AI) is rapidly transforming healthcare, medical curricula have not fully adapted to this transformation, particularly in developing countries. This gap is especially pronounced in non-metropolitan regions, where resources and exposure to technology may be more limited. Understanding the perspectives of medical students in these specific contexts is vital for designing effective and equitable educational strategies.ObjectiveThis study evaluated the knowledge, awareness, attitudes, and educational expectations of students at a newly established Turkish medical school, located in a non-metropolitan city, regarding AI and digital health technologies.MethodsA descriptive, cross-sectional survey was conducted among first- to fourth-year students at Samsun University Faculty of Medicine. Data were collected from 198 participants, and a stratified random sample of 120 students was selected for analysis. The questionnaire covered demographics, digital literacy, AI knowledge, and attitudes toward its integration into the curriculum.ResultsThe majority of students rated their digital competence as moderate (59.2%) or low (19.2%). Interest in technology was highest among first-year students (60%) but declined significantly to 13.3% by the fourth year. Knowledge of AI was generally limited, with only 15.8% reporting a high level of knowledge and 55.0% stating they conducted little or no independent research on AI. Despite these deficiencies, students expressed strong support for AI integration: 78.3% supported AI-assisted interactive tools, 79.2% endorsed personalized learning, and 80% acknowledged the role of AI in clinical decision-making processes. The majority of students (82.5%) advocated for a broader integration of AI, stating that their top priority was its integration into clinical practice (39.2%).ConclusionOffering a rare perspective from a non-metropolitan city in a developing country, this study reveals that medical students exhibit high motivation for AI integration despite significant knowledge gaps. This enthusiasm presents a critical opportunity for curriculum reform. There is an urgent need for context-appropriate AI curricula to bridge the gap between student interest and preparedness, thereby empowering the next generation of physicians in diverse settings for the future of digital healthcare.